Carboxymethyl cellulose binders enable high-rate capability of sulfurized polyacrylonitrile cathodes for Li–S batteries. Issue 11 (27th February 2017) - Li, Yang; Zeng, Qingcong (Ray); Gentle, Ian R.; Wang, Da-Wei
Abstract : Water-processable binders improved the electrode polarity and wettability. Li–S batteries consisting of such binders exhibited superior performance at high current densities. Abstract : Li–S batteries have attracted ever-increasing interest in recent years due to their high theoretical specific energy. However, the cycling and rate performance of the sulfur cathode are seriously hindered by the notorious polysulfide dissolution and its low conductivity. Sulfurized carbon materials containing covalently bonded sulfur chains have shown relatively better stability for Li–S batteries. In this study, we report the improvement of the high-rate performance of sulfurized carbon cathodes derived through vulcanization of polyacrylonitrile. We compared sodium carboxymethyl cellulose (NaCMC) with poly(vinylpyrrolidone) (PVDF) as cathode binders for the sulfurized polyacrylonitrile (SPAN) electrode. The SPAN cathode using the NaCMC binder showed a capacity of 938 mA h g −1 after 450 cycles at 0.9C rate (1C = 1675 mA h g −1 ) and a capacity of 677 mA h g −1 at 5C rate; both performances are much superior to that of the SPAN cathode using the PVDF binder. This result illustrates the feasibility of using water-soluble oxygen-containing binders to improve the C-rate performance of sulfurized carbons.